2015
DOI: 10.3382/ps/pev262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-encapsulated and pro-encapsulated Enterococcus faecalis on growth performance, blood characteristics, and cecal microflora in broiler chickens

Abstract: The effects of microencapsulation of Enterococcus faecalis on the growth performance, antioxidant activity, immune function, and cecal microbiota in broilers were investigated. Broilers (1-day-old) were assigned randomly as follows: 5 treatments, 5 replicate pens per treatment, and 20 broilers per pen. Treatments included (1) a basal diet (CON), (2) CON + Aureomycin (1 g/kg of diet) (ANT), (3) CON + free non-encapsulated probiotics (1 × 10(9) cfu/kg of diet) (FREE), (4) CON + pro-encapsulated probiotics (1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Consistent with this broad generalization, the gut microbiota of Greylag geese were also occupied by these four phyla (Supporting Information Table S2). The positive relationship between Firmicutes abundance and body mass gain had been reported in chickens . The predominance of Firmicutes present in Greylag geese gut microbiota may also be possibly related to the weight gain required for the demands of long distance migration (sampling was conducted during their autumn migration).…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this broad generalization, the gut microbiota of Greylag geese were also occupied by these four phyla (Supporting Information Table S2). The positive relationship between Firmicutes abundance and body mass gain had been reported in chickens . The predominance of Firmicutes present in Greylag geese gut microbiota may also be possibly related to the weight gain required for the demands of long distance migration (sampling was conducted during their autumn migration).…”
Section: Discussionmentioning
confidence: 84%
“…Alkhalf, Alhaj, and Al-Homidan (2010) reported that higher level of the supplementation probiotic to broilers in the levels of 0.8 -1 g kg -1 was found to be better than control. Increasing levels of encapsulated probiotic could improve viability and stability, increase protection against pathogenic resulting in improving in nutrient utilization, gut environment, and growth performance (Natsir et al, 2018;Zhang et al, 2015).…”
Section: The Effect Of Probiotic Supplementation Either Powdered or Ementioning
confidence: 99%
“…In this research, we use either without encapsulation or encapsulation technology to protect probiotics. Because encapsulation technology has been observed to be a protector for corematerial (either pro or prebiotic), this is an effective way to maintain viability, survivability and protect from environmental barriers inside, against pathogenic bacteria, enhance immune function and growth performances (Natsir et al, 2019;Ritzi, Abdelrahman, Mohnl, & Dalloul, 2014;Yazhini, Visha, Selvaraj, Vasanthakumar, & Chandran, 2018;Zhang et al, 2015). Supplementation of either powdered or encapsulated probiotic is expected to improve production performances.…”
Section: Introductionmentioning
confidence: 99%
“…However, lactic acid bacteria are very sensitive to the external environment, such as feed process, storage, and gastrointestinal tract of animal (Corona-Hernandez, Alvarez-Parrilla, Lizardi-Mendoza, Islas-Rubio, & de la Rosa, 2013;Prakash, Tomaro-Duchesneau, Saha, & Cantor, 2011). Microencapsulated probiotics have beneficial effects on enhancing the survivability of probiotics to the adverse environment in the gastrointestinal tract and on improving the overall health of broilers (Corona-Hernandez et al, 2008;Zhang, Li, Yun, Qi, et al, 2015b). Furthermore, the antimicrobial protein produced by E. faecalis showed antibacterial activity against Escherichia coli, so E. faecalis might be used for inhibition of the growth of pathogenic bacteria (Pantev et al, 2003;Shekh & Roy, 2012).…”
Section: Introductionmentioning
confidence: 99%